2012
DOI: 10.1021/ed200015v
|View full text |Cite
|
Sign up to set email alerts
|

Organic Mastery: An Activity for the Undergraduate Classroom

Abstract: A group activity for use in the classroom or recitation section of an organic chemistry course is described. This activity, a board game using trivia and concepts from the course material, can be used periodically throughout the semester to introduce or reinforce content knowledge. Alternate versions can be easily constructed for other courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…The results revealed that the students, especially the low and middle achievers, learned better chemistry concepts with considerably more enjoyment and pride and less anxiety and boredom than their peers in the comparison class. Similar positive results of implementing board and card games instruction on achievement (Dieser & Bogner, 2016;Ng al., 2007, May;Rastegarpour & Marashi, 2012), enjoyment (Mariscal et al, 2012;Morris, 2011;Mosher et al, 2012;Ng et al, 2007, May;Rastegarpour & Marashi, 2012), and anxiety (Hung et al, 2014) were found to those in the literature. Rastegarpour and Marashi (2012) investigated the effects of a card game, a computer game, and the traditional teaching method on learners' chemistry concepts and revealed that teachermade instructional card games are effective for learning chemistry.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The results revealed that the students, especially the low and middle achievers, learned better chemistry concepts with considerably more enjoyment and pride and less anxiety and boredom than their peers in the comparison class. Similar positive results of implementing board and card games instruction on achievement (Dieser & Bogner, 2016;Ng al., 2007, May;Rastegarpour & Marashi, 2012), enjoyment (Mariscal et al, 2012;Morris, 2011;Mosher et al, 2012;Ng et al, 2007, May;Rastegarpour & Marashi, 2012), and anxiety (Hung et al, 2014) were found to those in the literature. Rastegarpour and Marashi (2012) investigated the effects of a card game, a computer game, and the traditional teaching method on learners' chemistry concepts and revealed that teachermade instructional card games are effective for learning chemistry.…”
Section: Discussionsupporting
confidence: 50%
“…Board and card game studies have reported that GBL is enjoyable for learning science and mathematics (Mariscal et al, 2012;Morris, 2011;Mosher et al, 2012;Ng et al, 2007, May;Rastegarpour & Marashi, 2012). A survey by Ng et al (2007, May) revealed that 87.7% of students enjoy mathematical card games.…”
Section: Effects Of Educational Games On Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of game-based learning in the classroom was a board game implemented in an undergraduate setting in an organic chemistry course [9]. The design of the board itself was modeled after an exothermic reaction.…”
Section: Game-based Learningmentioning
confidence: 99%
“…The game was introduced prior to the students taking a test for the course, and the students who were exposed to the game received better overall test scores than those who only experienced the typical "question and answer" review sessions. The participants enjoyed the game and looked forward to playing it as a part of their review session [9].…”
Section: Game-based Learningmentioning
confidence: 99%